2007
DOI: 10.1128/mcb.01974-06
|View full text |Cite
|
Sign up to set email alerts
|

Specific Phosphorylation of p120-Catenin Regulatory Domain Differently Modulates Its Binding to RhoA

Abstract: p120-catenin is an adherens junction-associated protein that controls E-cadherin function and stability. p120-catenin also binds intracellular proteins, such as the small GTPase RhoA. In this paper, we identify the p120-catenin N-terminal regulatory domain as the docking site for RhoA. Moreover, we demonstrate that the binding of RhoA to p120-catenin is tightly controlled by the Src family-dependent phosphorylation of p120-catenin on tyrosine residues. The phosphorylation induced by Src and Fyn tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 38 publications
2
114
0
1
Order By: Relevance
“…Exons for human and zebrafish p120 catenin d1 found in the UCSC genome database are similar but not identical. Six tyrosine and four serine and threonine residues that are phosphorylated in humans are conserved in zebrafish; two tyrosine and four serine threonine residues are absent from the zebrafish sequence, suggesting that they may not be essential residues (human: tyr-96, -112, thr-310, and ser-122, 312, -873), although tyr-112 is implicated in RhoA GTPase binding (Castaño et al, 2007).…”
Section: Results P120 Catenin D1 Is the Most Highly Expressed P120 Camentioning
confidence: 99%
“…Exons for human and zebrafish p120 catenin d1 found in the UCSC genome database are similar but not identical. Six tyrosine and four serine and threonine residues that are phosphorylated in humans are conserved in zebrafish; two tyrosine and four serine threonine residues are absent from the zebrafish sequence, suggesting that they may not be essential residues (human: tyr-96, -112, thr-310, and ser-122, 312, -873), although tyr-112 is implicated in RhoA GTPase binding (Castaño et al, 2007).…”
Section: Results P120 Catenin D1 Is the Most Highly Expressed P120 Camentioning
confidence: 99%
“…Previous studies have suggested that phosphorylation of a number of tyrosine residues within the p120 regulatory domain may play a role in p120 signaling (Mariner et al, 2004;Shibata et al, 2004;Castano et al, 2007;Reynolds, 2007). Therefore, we investigated whether H. pylori infection similarly altered levels of p120 tyrosine phosphorylation.…”
Section: H Pylori Strain 713 Alters the Phosphorylation State Of P120mentioning
confidence: 99%
“…Phosphorylation of p120 has been extensively mapped, and it has been shown that the majority of the phosphorylated tyrosines, serines and threonines are in a 100 amino acid region in the amino terminus, termed the p120 regulatory domain that is important for signal integration from non-receptor kinases [14,16,38]. Threonine 310 is within the regulatory domain, while threonine 916 is in the carboxyl terminus outside of the regulatory domain.…”
Section: The Phosphorylation Domain Of P120 Regulates the Dynamics Ofmentioning
confidence: 99%
“…On the other hand, Ozawa and Ohkubo found that tyrosine phosphorylation of p120 in v-Src transfected Ecadherin-expressing L cells led to reduced cell-cell adhesion without influencing the affinity of p120 for E-cadherin [11]. In addition to its role in regulating E-cadherin function, p120 also functions as a Rho guanine nucleotide dissociation inhibitor, or Rho GDI [12,13], and Castano et al recently showed that this function of p120 is regulated by Fyn/Src-dependent tyrosine phosphorylation [14].…”
Section: Introductionmentioning
confidence: 99%